Policy competition and policy cooperation in a monetary union - Carlberg, Michael (Berlin : Springer, 2004)
Studies the interactions between monetary and fiscal policies in the Euro area. It also discusses the case for central bank independence and fiscal cooperation.
Includes bibliographical references (p. [273]-283) and index.
oif 31/08/15
Loan
Keywords: Monetary policy; Economic policy; Monetary unions; International economic relations; Macroeconomics